2022
DOI: 10.3390/v14050872
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Approaches for SARS-CoV-2 Detection: Harnessing for Application in Food and Environmental Samples

Abstract: The public health crisis caused by the emergence of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in 2019 has drastically changed our lifestyle in virtually all contexts around the world. SARS-CoV-2 is mainly airborne, transmitted by the salivary droplets produced when infected people cough or sneeze. In addition, diarrhea symptoms and the detection of SARS-CoV-2 in feces suggest a fecal–oral route of contagion. Currently, the high demand for SARS-CoV-2 diagnosis has surpassed the availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…60 In addition, the LC−MS LOD for Influenza A hemagglutinin 61 is 30,000 fg/mL, and for RSV, it is 40,000 fg/ mL. 61 Thus, the GEMS has a 1 to 2 orders of magnitude better LOD than LC−MS. A much better LOD of 10 viruses/L has been achieved via RT-qPCR; 62 however, similar to LC−MS, this requires a lab setting to perform the concentration and additionally relies on amplification requiring complex machinery and chemicals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 In addition, the LC−MS LOD for Influenza A hemagglutinin 61 is 30,000 fg/mL, and for RSV, it is 40,000 fg/ mL. 61 Thus, the GEMS has a 1 to 2 orders of magnitude better LOD than LC−MS. A much better LOD of 10 viruses/L has been achieved via RT-qPCR; 62 however, similar to LC−MS, this requires a lab setting to perform the concentration and additionally relies on amplification requiring complex machinery and chemicals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For LC–MS, various studies have found LOD 3000 fg/mL for SARS-CoV2 in nasopharynx samples, , and while LC–MS has been used to detect it in wastewater, no LOD has been reported . In addition, the LC–MS LOD for Influenza A hemagglutinin is 30,000 fg/mL, and for RSV, it is 40,000 fg/mL . Thus, the GEMS has a 1 to 2 orders of magnitude better LOD than LC–MS.…”
Section: Resultsmentioning
confidence: 99%